Zeolite Imidazolate Framework 8 (ZIF-8) Decorated on ZnO Nanorods Resulting in Layered Double Hydroxide Layers for Determination of Phenolic Pollution in Water - Marzieh Piryaei; Mir Mahdi Abolghasemi; Sona Hasani (Nanochemistry Research)
This study investigated the use of ZnO nanorods, made from layered double hydroxide layers and decorated with Zeolite imidazolate framework 8 (ZIF-8), as a new coating for solid-phase microextraction fiber (SPME). The effectiveness of the fabricated fiber in extracting phenolic compounds from the water sample was evaluated using gas chromatography-mass spectrometry. The effect of effective parameters, such as ionic strength, temperature, and extraction time, was examined to determine the ideal conditions. The calibration curves had a range of 0.01–300 ng mL-1 and acceptable linearity (R2 > 0.995). The limits of detection were between 0.003 and 0.11 ngmL-1, with a relative standard deviation of less than 8.4% under ideal conditions. The model was evaluated using river water and wastewater samples. The results showed that the proposed method is a straightforward, effective, and environmentally friendly approach for the quick and practical determination of phenolic compounds in real samples.